FORMULATION AND EVALUATION OF CELECOXIB CREAM AND ITS RELEASED STUDY - ANWAR, SADIA; JAN, SYED UMER; GUL, RAHMAN (International Journal of Current Pharmaceutical Research, 2020)
Objective: The purpose of this study was to formulate and evaluate of Celecoxib cream and it’s in vitro release study. Methods: The release study was conducted, using dialysis cellulose membrane, in Franz cells. The donor chamber was filled with phosphate buffer pH 7.4, released medium were analyzed by UV-Vis spectrophotometer at 250 nm. Kinetics model was used for calculations. The cream was followed by different evaluations like pH measurement, homogeneity, spreadability, stability study, drug content, SEM, XRD studies and skin irritation test was used for the reliability of physical conditions and chemical relation. DD solver and SPSS were used for statistical analyzation of the data. Results: The best in vitro drug release profile achieved with thyme oil in Celecoxib cream. Formulation F2 showed the highest (83%) released. The results of the Celecoxib (1%) were suitable in all constraints. The prepared Celecoxib cream was encouraging for the formulation of transdermal drug delivery. Conclusion: The Celecoxib cream was successfully prepared and could be beneficial for transdermal drug delivery.